Evidence-Based Policing of U.K. Muslim Communities: Linking Confidence in the Police With Area Vulnerability to Violent Extremism. (March 2015) - Murray, Alex; Mueller-Johnson, Katrin; Sherman, Lawrence W.
Preventing the growth of political views justifying violence is central to global strategies for countering terrorism. In Western democracies, targeting resources on local "hot spots" of low confidence in the police is essential for making these strategies evidence based. This research explores the relationship between two kinds of evidence for targeting resources across 335 neighborhoods in a large metropolitan area: police scoring of human intelligence data and public opinion surveys ( N = 30, 412). We map the intelligence data by classifying each Census Output Area (COA) as high, medium, or low risk of vulnerability to violent extremism. Independent survey data for each neighborhood that measures confidence in the police is then compared to categorizations of vulnerability from intelligence sources. The results suggest that while Muslim respondents have lower levels of confidence in the police than other ethnic minority groups, their confidence levels are even lower in areas where intelligence suggests the greatest risk of extremist violence. Given the convergence of indicators of COAs with lowest confidence in police and highest risk of extremist violence, the value of combining these measures appears substantial for evidence-based targeting of "hearts and minds" strategies for preventing extremist, pro-violence views.